A natural interomone 2-methyl-2-butenal stimulates feed intake and weight gain in weaned pigs. (13th July 2016) - McGlone, J. J.; Thompson, G.; Devaraj, S.
Abstract : A novel approach to potentially improve pig growth and welfare is to supplement environments with biologically meaningful odors that are deficient. The post-weaning environment lacks maternal odors that may contribute to the often-observed post-weaning lag in growth and health challenges. A recently reported rabbit maternal pheromone (2-methyl-2-butenal (2M2B)) may act as an interomone in the pig. The objective of this study was to determine if providing a maternal pheromone/interomone during transport and the post-weaning environment may enhance pig performance. A total of 40 replicated pens were used in a factorial arrangement of two transport olfactory experiences (Control v . 2M2B), two nursery olfactory experiences (Control v . 2M2B) and two sexes (barrow v . gilt). Pig body weight, average daily gain (ADG), average daily feed intake (ADFI) and gain : feed ratio (G : F) were measured and calculated over a 28-day post-weaning period. Pig sex and application of 2M2B during transport had no effect on pig performance. However, pigs that had 2M2B applied to their feeder at weaning had 15% greater feed intake (0.74 v . 0.64±0.03 kg/day, P <0.01) and 12% greater ADG (0.27 v . 0.24 kg/day, P <0.05) than control pigs. G : F ratio was not different between treatments. The interomone 2M2B is a novel, safe molecule that can improve pig post-weaning performance. This report highlights a new area of study and a natural class of compounds that can improve pig performance and potentially improve pig welfare.